2018
DOI: 10.1039/c7cp06279f
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline and CN-functionalized polyaniline as organic cathodes for lithium and sodium ion batteries: a combined molecular dynamics and density functional tight binding study in solid state

Abstract: We present the first atomistic-scale simulation of the discharge process of polymeric cathode materials for electrochemical batteries in solid state. The oxidation of polyaniline (PANI) and of cyano groups (CN) functionalized PANI induced by coordination to the electrolyte anions is computed and voltage curves are estimated. To deal with the large required numbers of atoms and structures, a combination of molecular dynamics and density functional tight binding (DFTB) is used. The DFTB is benchmarked to density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…These studies demonstrated the computational capability in studying organic electrode materials. Recently, computational studies were extended to novel compounds, such as polyaniline (PANI), tetracyanoethylene (TCNE), etc., as potential electrodes for NIBs.…”
Section: Positive Electrode Materialsmentioning
confidence: 99%
“…These studies demonstrated the computational capability in studying organic electrode materials. Recently, computational studies were extended to novel compounds, such as polyaniline (PANI), tetracyanoethylene (TCNE), etc., as potential electrodes for NIBs.…”
Section: Positive Electrode Materialsmentioning
confidence: 99%
“…1 and 2 eV, respectively (Legrain and Manzhos, 2015;Lüder et al, 2017a,b). Adding/replacing electron-withdrawing groups, e.g., F atoms or cyano (CN) groups, in a molecular structure can also increase the voltage by increasing the binding strength to the active cation (Chen and Manzhos, 2016c;Chen et al, 2018). Doping is only one way to affect the performance of batteries and it is particular in that it directly addresses the electronic structure of a material.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we focus on materials that work by reduction, i.e., in materials in which the lowest unoccupied molecular orbital (LUMO) of the electrode determines the redox potential. For materials that work by oxidation, the HOMO (highest occupied molecular orbital) determines the voltage and effective strategies there can be different (Geniès et al, 1989;Chen and Manzhos, 2016c;Rodriguez-Pérez et al, 2016;Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results with ML based DFTB parameterization to date suggest that ML could be efficient to achieve accurate DFTB modeling of organic battery materials. This is especially important for modeling of polymeric materials (requiring relatively large scale models to account for amorphous character) and of realistic charge-discharge dynamics [159].…”
Section: Discussionmentioning
confidence: 99%